EFEKTIVITAS WARM COMPRESS DAN DYNAMIC STRETCHING TERHADAP NYERI PUNGGUNG BAWAH NON-SPESIFIK - Khalida Nur Rahma; Saifudin Zuhri; Yoni Rustiana (Jurnal Nasional Fisioterapi, 2023)
Background: Humans fulfill their living needs with static work cycles over long periods of time, such as batik workers. This has an impact on the occurrence of non-specific low back pain (NPB). Physiotherapy technology to reduce pain in non-specific NPB includes warm compression and dynamic stretching. Objective: To determine the effectiveness of warm compression and dynamic stretching in reducing pain in non-specific NPB of batik workers. Method: pre and post-test with control group design. Subjects: 29 subjects, warm compress and dynamic stretching group n=15 (15 women) and control group n=14 (1 man and 13 women). 3 subjects dropped out, namely 2 subjects from the intervention group and 1 subject from the control group. The warm compress intervention was carried out for 15 minutes and dynamic stretching consisted of 8 movements, carried out 3 times a week for 4 weeks. The results of the statistical analysis of the pre-post difference test obtained a value of p=0.000 (warm compress and dynamic stretching group) and the results of the pre-post difference test obtained a value of p=0.824 (control group). The results of the post-test difference between the intervention group and the control group obtained a value of p=0.015. Conclusion: Warm compression and dynamic stretching are effective in reducing pain in non-specific NPB.